The Impact of Air Pollution on the Course of Cystic Fibrosis: A Review - Blayac, Marion; Coll, Patrice; Urbach, Valérie; Fanen, Pascale; Epaud, Ralph; Lanone, Sophie (Frontiers in Physiology, 2022)
Cystic fibrosis (CF) is a lethal and widespread autosomal recessive disorder affecting over 80,000 people worldwide. It is caused by mutations of the CFTR gene, which encodes an epithelial anion channel. CF is characterized by a great phenotypic variability which is currently not fully understood. Although CF is genetically determined, the course of the disease might also depend on multiple other factors. Air pollution, whose effects on health and contribution to respiratory diseases are well established, is one environmental factor suspected to modulate the disease severity and influence the lung phenotype of CF patients. This is of particular interest as pulmonary failure is the primary cause of death in CF. The present review discusses current knowledge on the impact of air pollution on CF pathogenesis and aims to explore the underling cellular and biological mechanisms involved in these effects.